Preferensi Masyarakat Kota Samarinda terhadap Bank Syariah - Mursyid Mursyid (Fakultas Syariah Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, Indonesia, 2011)
The study seeks to explore the preferences of the Samarinda’s people against Islamic bank. In order to encourage the development of sharia banking nationally, needed to expand sharia banking network in pontetial areas and require the service of sharia banking. Sharia banking network expension is market driven, based on need n willingness of bank to provide an overview of sharia banking development pontential. Potential meant can be viewed from a resource and area economic activities and the customer preferences to sharia banking product and service, then the research preferences of samarinda people is required. Grand mean analysis get number 7,69 from 300 respondent, its mean that majority of sample thought that sharia banking can be alternative when conventional bank. Regression analysis result indicate that the presence of shariah banking in samarinda city prospectively, because 91,13% of people samarinda were muslim.